Labour conditions in regional versus global value chains: Insights from apparel firms in Lesotho and Eswatini - Giovanni Pasquali (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
We explore how decent work varies across Southern Africa apparel firms participating in global value chains (GVCs) and regional value chains (RVCs), respectively. We draw on crosssection survey data from 135 workers in 31 firms across Eswatini and Lesotho, two large apparel exporters serving both global and regional markets. We use a linear probability model to estimate how measurable standards and enabling rights vary depending on whether supplier firms participate in GVCs or RVCs. Our results show that whilst private audits are significantly more likely to take place among GVCs suppliers, these only reflect higher measurable standards in terms of paid sick leave, maternity leave, and production bonuses. However, no major difference emerges, with workers' conditions being fairly poor across GVCs and RVCs. Importantly, other factors such as ownership, country legislation, firm size, and gender are critical in explaining variations in decent work.
Keywords: O55; J83; 330; regional value chains; global value chains; decent work; apparel; Lesotho; Eswatini; firms